Deteksi Senyawa Bioaktif Rotifera Brachionus rotundiformis dari Perairan Laut Sulawesi Utara - Joice R.T.S.L Rimper (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
Rotifers are one potential plankton to have bioactive compounds. This study is an initial step to reveal the presence of bioactive compounds in rotifers and is expected to bring a breakthrough in the discovery of indigenous bioactive compounds. Plankton was collected with plankton nets by pulling the nets horizontally on the surface of the waters. For extraction, Brachionus rotundiformis was cultured with different salinity. Micro algae were used as rotifer feed. It is a kind of Nannochloropsis oculata. with salinity of 4 ppt, 40 ppt, 50 ppt and 60 ppt. Tested bacteria was Vibrio cholerae, Bacillus subtilis and Escherichia coli. Comparator antibiotics were amoxicillin and tetracycline. Paper disc method was used measure antibacterial activity. Antibacterial activity of B. rotundiformis was measured. Antibacterial activity of B. rotundiformis was measured. They were cultured on salinity of 4 ppt, 20 ppt, 40 ppt, 50 ppt, 60 ppt with N.oculata feed. The resullts showed most large clear zone formed by B. rotundiformis cultured on 40 ppt salinity to inhibit E. coli, it was 4.66 mm in diameter. In general, 40 ppt salinity is the most potential trigger of B. rotundiformis to produce antibacterial compounds compared with lower or higher salinity. The antibacterial activity was affected by different salinity.